Status and Barriers of Classroom-based student Assessment Practices in Geography at Secondary level in Nepal - Khatiwada, Shambhu Prasad (Interdisciplinary Research in Education, 2019)
The main focus of this article is to analyze the status and barriers to effective use of classroom-based student assessment practices for geography teacher at secondary levels. The data for this paper were generated from the empirical study. The purposive sampling method was used to select both communities (12) and institutional (4) schools from different Provinces as well as ecological zones. This paper concludes that the majority of geography teachers still use traditional means of student assessment practices, such as terminal exams, half-yearly exams, and annual exams. Some teachers have used both the paper-pencil test and classroom-based student assessment practices in general and particular in geography subject. But the number of such teachers is very low. The classroom-based student assessments such as homework, classwork, group discussion, project work and so on are an integral part of geography teaching. This paper has also identified barriers to the effective use of classroom-based assessment practices.